The answer of this question could be calculated in this way:

```
Sum ( the kth Fibonacci number * 2 ^ (n+1-k) ) with k=1 to n+1
```

The Fibonacci numbers are: 1, 1, 2, 3, 5, 8, 13.....

For examples:

```
N = 2
Answer = 1 * 4 + 1 * 2 + 2 * 1 = 8
N = 3
Answer = 1 * 8 + 1 * 4 + 2 * 2 + 3 * 1 = 19
N = 4
Answer = 1 * 16 + 1 * 8 + 2 * 4 + 3 * 2 + 5 * 1 = 43
N = 5
Answer = 1 * 32 + 1 * 16 + 2 * 8 + 3 * 4 + 5 * 2 + 8 * 1 = 94
```

I didn't chance upon the rule and the strict demonstration is not complex, but it is not my point. **If you have any doubts, please point out the reason.**

The general formula of Fibonacci is here: https://en.wikipedia.org/wiki/Fibonacci_number

The general formula of Geometric progression: https://en.wikipedia.org/wiki/Geometric_progression

Finally we can get the general formula of these question after some math evolution.

```
n = n + 1
a = (1 + 5**0.5) / 4
b = (1 - 5**0.5) / 4
res = 2**n / 5**0.5 * ((1 - a**n) / (1 - a) * a - (1 - b**n) / (1 - b) * b)
```

Unfortunately, the float is too long to keep accurate.